Clinical characteristics and survival analysis of Chinese ovarian cancer patients with RAD51D germline mutations - Hongwen Yao; Ning Li; Hua Yuan (BMC Cancer, 2022)
Abstract Objectives We aimed to describe the behavior among Chinese ovarian cancer patients with RAD51D germline mutations at our institution. Methods Next-generation sequencing (NGS) was conducted for the entire coding regions and exon/intron boundaries of the RAD51D genes in 781 Chinese ovarian cancer patients treated at our institution from January 1, 2015 to August 1, 2021. Clinicopathological characteristics, treatment modalities, and outcomes were assessed for ovarian cancer patients with RAD51D germline mutations. Results RAD51D germline pathogenic mutations were detected in 1.7% (13/781) of patients in this cohort. RAD51D c. 270_271dup (p. Lys91fs) mutation was the most common mutation which was found in 7 patients (7/13, 53.1%). Patients median age at diagnosis was 58 years (range: 45–69 years). 46.2% (6/13) of them were diagnosed after 60 years. Only 1 patient (1/13, 7.7%) had a family history of ovarian or breast cancer. And 1 patient (1/13, 7.7%) had a personal history of breast cancer. The FIGO 2014 distribution by stage was: stage II in 1 patient (7.7%), stage III in 9 patients (69.2%) and stage IV in 3 patient (23.1%). 92.3% (12/13) patients had high-grade serous carcinoma. 2 patients (2/13, 15.4%) had a primary peritoneal cancer. The majority of patients in the entire cohort were reported to be platinum sensitive (92.3%, 12/13) with a platinum-free interval (PFI) of > 6 months. For patients who received PARPis for 2nd line maintenance treatment (n = 5), 2 patients discontinued PARPis treatment after 33.5 and 8.1 months of duration. Other 3 patients are still on therapy with a duration of 2.4, 13.8 and 30.1 months at the date of data cutoff. 1 patient received PARPi as salvage treatment with a duration of only 1.2 months. Nine patients (9/13, 69.2%) relapsed during follow up and all of them relapsed within 2 years after diagnosis, among which 88.9% (8/9) were classified as platinum-sensitive recurrence (PSR), and only 1 patient was classified as platinum-resistant recurrence (PRR). Median PFS for the entire cohort was 17.3 months. Median PFS for the PSR subgroup was 15.9 months. 2 patients died during follow-up. The OS of these 2 patients was 17.2 and 39.6 months. The 5-year OS rate was 67.5%. Conclusions RAD51D germline mutations are more frequent in Chinese ovarian cancer patients than other population. Few patients have a family history of ovarian or breast cancer, and personal history of breast cancer. Most patients are diagnosed after 50 years. The sensitivity to PARP inhibitors of patients with RAD51D germline mutations need a further analysis.